Blockchain and Value Co-Creation: Strategies to Improve Human Resource Performance in the Islamic Banking Industry - Satria Avianda Nurcahyo; Setya Indah Isnawati; Aris Puji Purwatiningsih; MA Irfan Rahmana (Universitas Islam Negeri (UIN) Walisongo Semarang, 2025)
Purpose - This study aims to explore how the application of blockchain technology can contribute to improving human resource (HR) performance through a value co-creation strategy at PT Bank Syariah Indonesia, Central Java Province. This study uses a qualitative approach with an in-depth interview method with employees at the managerial level to collect relevant data. Blockchain, as a technology known for its security and transparency, is expected to improve operational efficiency and collaboration between departments, which in turn has an impact on improving HR performance. Method - The method used in this study is qualitative, which is a research approach used to understand social phenomena in depth, from a complex and contextual perspective. In qualitative research, data is collected in a way that allows researchers to explore the feelings, thoughts, and experiences of respondents, and to understand the context in which the phenomenon occurs. Result - This study identified that blockchain can improve trust and communication between management and employees, creating a more cooperative and dynamic work environment. This allows companies to respond to market changes more quickly and efficiently. The study also revealed that blockchain can reduce administrative and operational costs through the automation of processes that previously required human intervention, such as payroll and contract management. The study concluded that value co-creation strategies supported by blockchain technology can be an effective tool in improving HR performance in the Islamic Banking industry. Implication - Recommendations for further implementation include training and developing employee skills in using blockchain technology as well as improving the company's information technology infrastructure to support this digital transformation. Originality - Blockchain, as a technology known for its security and transparency, is expected to improve operational efficiency and collaboration between departments, which in turn has an impact on improving HR performance. The findings of this study indicate that the implementation of blockchain can strengthen the HR management system through the creation of shared value (value co-creation) between management and employees. Keywords: Blockchain, Value Co-Creation, HR Performance, Islamic Banking Industry.